ASSOCIATION BETWEEN MEDICATION ADHERENCE AND QUALITY OF LIFE AMONG PATIENTS WITH CORONARY ARTERY DISEASE DURING PANDEMIC COVID-19 AT PRIVATE HOSPITAL TYPE A BANDUNG-INDONESIA - Muhammad Deri Ramadhan; Eny Kusmiran; Istianah Istianah; Destiya Dwi Pangestika (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The prevalence of coronary artery disease (CAD) is increasing and becomes a major health problem nowadays. CAD has an impact on various aspects of the sufferer's life, both physical, psychosocial, and spiritual which affect the patient's Quality of Life (QOL). The main effort that can be done to maintain or improve the quality of life is with the patient's medication adherence. The existence of social restrictions during the COVID-19 pandemic has become a current issue regarding access to treatment of patients with CAD in hospitals so it has not been depicted regarding medication adherence and quality of life of patients with CAD during the pandemic, especially in Indonesia. This study aims to analyze the association between medication adherence and the quality of life of patients with CAD during the COVID-19 pandemic. The study method used is analytical observational with a cross-sectional approach. Primary data were collected from patients with CAD who were outpatient at the Cardiology Clinic of Private Hospital Type A in Bandung, Indonesia with accidental sampling technique. The study was conducted in January 2022 with the minimum sample being 70 respondents (Slovin formula). Data collection uses The Modified-Morisky Adherence Scale-8 (MMAS-8) questionnaire to assess medication adherence and the Seattle Angina Questionnaire-7 (SAQ-7) Questionnaires to assess the quality of life of patients with CAD. The statistical test is Chi-Square. The result showed that 34 (48.6%) respondents had low medication adherence and 43 (61.4%) respondents had good QOL. There was an association between medication adherence and QOL (p-value 0.009). Adhering to treatment can improve the quality of life of patients with CAD.